Matching starter phenotype to functionality for low salt Cheddar cheese production based on viability, permeability, autolysis, enzyme accessibility and release in model systems. (June 2020) - Yanachkina, Palina; Doolan, Imelda; LaPointe, Gisele; Wilkinson, Martin G.
Abstract: Lactococcal starters were evaluated for suitability in low salt Cheddar cheese manufacture using model systems containing 0%, 3% or 5% (w/v) salt. Strains underwent the Pearce test and storage at 14 days and were monitored for viability, permeabilisation, autolysis, PepX activity and cell envelope proteinase activities. Salt exerted a species and strain-dependent effect on viability throughout storage. Flow cytometry indicated live, permeabilised or dead cells varied in a strain and salt-dependent manner. Salt affected the dynamics of live and permeabilised cells during storage; cooking temperature influenced permeability and accessible intracellular PepX activity. Higher permeabilisation, autolysis, released and accessible intracellular PepX activity with lower cell envelope proteinase activities, indicated AM2, SK11 and Z8 strains may perform better in reduced salt environments. Strains HP, R1 and 303 had low autolysis and permeabilisation but higher cell envelope proteinase activities at reduced salt levels and may not be suitable for low salt cheese production.